2018
DOI: 10.1002/ajhb.23184
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of self‐reported heights and weights in a predominately low‐income, diverse population living in the USA

Abstract: Objectives: This study explored the accuracy of self-reported heights and weights and factors associated with self-reported bias in a diverse American sample. Methods: Demographic, self-reported, and measured height and weight data from different studies with the same PI were compiled into one SPSS file and analyzed with paired t-tests to detect differences between self-reported and actual values. Kruskal-Wallis tests followed by pairwise t-tests detected differences among age, ethnicity, sex, income, and educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 42 publications
(66 reference statements)
4
21
0
Order By: Relevance
“…Fifth, we did not have a large enough sample size of non‐residential fathers to assess differences by residency status. Sixth, fathers in our study self‐reported height and weight, which may reflect over‐reported of height and under‐reported of weight 48 . A prior study of low‐income Black men in the US found that this mis‐reporting led to an under estimate of overall BMI, resulting in a misclassification of obesity by 5% 48 .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Fifth, we did not have a large enough sample size of non‐residential fathers to assess differences by residency status. Sixth, fathers in our study self‐reported height and weight, which may reflect over‐reported of height and under‐reported of weight 48 . A prior study of low‐income Black men in the US found that this mis‐reporting led to an under estimate of overall BMI, resulting in a misclassification of obesity by 5% 48 .…”
Section: Discussionmentioning
confidence: 73%
“…Sixth, fathers in our study self‐reported height and weight, which may reflect over‐reported of height and under‐reported of weight 48 . A prior study of low‐income Black men in the US found that this mis‐reporting led to an under estimate of overall BMI, resulting in a misclassification of obesity by 5% 48 . Finally, we did not assess maternal and paternal feeding style of infants beyond 12 months of age.…”
Section: Discussionmentioning
confidence: 84%
“…Fewer studies have explored the potential role of mental well‐being 10,23,27,28 . There is also evidence to suggest that the extent of misreporting and bias may differ across population subgroups 3,20,26,29 . Most germane to the present work are recent studies that have found that misreporting patterns differ in Hispanic and low‐income populations 3,20,26,29 …”
Section: Introductionmentioning
confidence: 77%
“…The collection of in-person anthropometric data, by trained research staff, and PA data via accelerometry is resource intensive for researchers and can place undue burden on participants. 3,36 Moreover, in-person data collection risks interruption in the event of largescale disasters. The accuracy afforded by objectively measured PA and anthropometrics often comes at the cost of not having a large sample size due to the feasibility of scaling up such resource intensive data collection.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we attempt to have no differences in weight status (BMI) between the mothers and their children of both regions, as the prevalence of overweight and obesity is higher in the South of Italy compared to the North (Gallus et al, 2013;Brunello and Labartino, 2014;Mancini et al, 2016). However, since the mothers reported their weight themselves, it is possible that some of them have underestimated their weight, particularly those who are overweight as found in the review of Gorber et al (2007) and by Opichka and Smith (2018).…”
Section: Research Considerations and Recommendationsmentioning
confidence: 99%